The Chirostylidae of southern Australia (Crustacea: Decapoda: Anomura) - Ahyong, Shane T.; Poore, Gary C.b. (Zootaxa, 2004)
The deep-water squat lobsters, Chirostylidae, of southern Australia are reported, comprising 31 species in three genera, increasing the known Australian fauna from 8 to 34. Two species of Eumunida Smith are reported, one of which, E. capillata de Saint Laurent & Macpherson, is a new record for Australia. Four species of Gastroptychus Caullery are reported, of which G. spinirostris is described as new, and G. hendersoni Alcock and G. sternoornatus Van Dam are new Australian records. A key to the Indo-West Pacific species of Gastroptychus is given. The known Australian fauna of Uroptychus Henderson is markedly increased from 4 to 26. Twenty-five species of Uroptychus are reported from the southern Australia. Twenty species of Uroptychus are described as new and two are reported for the first time from Australian waters. A key to the 26 known Australian species of Uroptychus is given. Uroptychus latirostris Yokoya from Japan, is removed from synonymy of U. cavirostris Alcock, from the Andaman Sea. The results of the present study indicate that the southern Australian chirostylid fauna is considerably more diverse than indicated by previous studies.